Identifikasi Komponen Kimia Saponin Greges Otot (Equisetum debile Roxb) Yang Berasal Dari Pallangga Kabupaten Gowa - Muhammad Khaerul Nur (Barongko: Jurnal Ilmu Kesehatan, 2022)
Has done research on the identification of the chemical components of saponin Greges muscle (Equisetum debile Roxb) derived from Pallangga Gowa. Greges muscle is a plant that is used by people who believed Pallangga empirically nutritious treat fever and diarrhea. This study aims to determine the chemical content of saponin extract from muscle Greges preliminary test to the use of Uv-Vis spectrophotometry. The process of isolation of chemical compounds including reflux extraction with methanol, n-butanol fractionation, isolation by Preparative Thin Layer Chromatography and purity testing. Isolation fraction of n-butanol extract of muscle Greges using eluent chloroform-methanol-water (8: 2: 1) yielded isolates 5 isolates were named A, B, C, D, and E. Isolates D and E followed by the separation process using Layer Chromatography thin and Two-dimensional thin Layer Chromatography. The results of a preparative Thin Layer Chromatography isolates D and E give the appearance of a single stain on the purity test that can be said is pure stain. The results of UV-Vis spectrophotometry analysis of Fraction D isolates obtained λ max with a peak wavelength of 536 nm and 550 nm which is characteristic of saponin compounds.